Rancang Bangun Alat Pendeteksi Status Pentanahan pada Instalasi Listrik Bangunan Berbasis Arduino Mega 2650 Pro - Corio, Dean; Andanu, Reva Arya; Miranto, Afit; Wahyu Pratama, Rizki (Jurusan Teknik Elektro Fakultas Teknik Universitas Bangka Belitung, 2022)
The grounding system is very important in a building electrical installation. The socket is an electrical installation component that functions as a power supply line to electronic equipment which in the PUIL 2000 rules must be connected to the building grounding system. As the installation age of a building increases, the grounding system will degrade. In this research, a grounding detector has been made at the socket to determine whether the socket is connected to the grounding system. In this tool there is a plug-shaped component that is mounted on a socket. From the test results, the tool can detect the voltage, leakage current and ground connectivity detection which is displayed on the LCD screen. The optocoupler sensor installed around the wheel can read the wheel rotation well so that the distance measurement data between the outlets has a good accuracy rate approaching 100%, namely 99.26%. The Arduino Mega 2560 Pro microcontroller manages the overall measurement data results and transfers the data to the memory card. The duration of use of this tool can be up to 10 hours, which is quite a long time to be used for the purpose of checking the grounding condition of a building with this tool.